Highly secured tunnel by optical crypto carrier transmission using ring resonator system - Soysouvanh, Saysamone; Mitatha, Somsak; Juleang, Pakorn (My University, 2017)
A new optical data transmission technique through a highly secure tunnel using a crypto carrier was investigated. High speed, high-security communication was achieved with an add/drop filter system and PANDA ring resonator optical equipment. The technique employed coding-decoding generated by public and private optical keys in frequency and time domains using a high-security tunnel. This novel technique provided high speed optical communication using light processing without electric control circuits. Restrictions on the operation of various equipment parameters affected the optical data communication signal intensity. The suitable signal ray data intensity was less than 200% of the signal ray intensity used for generating the optical public and private keys. This new technique ran and transmitted encrypted data efficiently to the receiver.
Keywords: optical communication; optical cryptography; ring resonator; security communication; soliton